2018
DOI: 10.1007/s10585-018-9908-8
|View full text |Cite
|
Sign up to set email alerts
|

Detection of melanoma metastases with the sentinel node biopsy: the legacy of Donald L. Morton, MD (1934–2014)

Abstract: Dr. Donald L. Morton was clearly the pioneer of the sentinel node biopsy, which was a major advance in oncology that has improved the management of cancer patients worldwide. He conducted a series of practice-changing clinical trials to validate the important staging role of the sentinel lymph node biopsy for melanoma, and also spawned other studies that demonstrated its staging value in multiple other cancer types, most notably in breast cancer, gastric cancer, and colorectal cancer. His many contributions in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The introduction of radiocolloid allows surgeons to perform preoperative lymphoscintigraphy to help guide surgical planning. 16 , 17 Moreover, it enables surgeons to employ intraoperative handheld gamma probe with or without an intraoperative portable gamma camera to locate lymph nodes with precision. 18 - 20 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The introduction of radiocolloid allows surgeons to perform preoperative lymphoscintigraphy to help guide surgical planning. 16 , 17 Moreover, it enables surgeons to employ intraoperative handheld gamma probe with or without an intraoperative portable gamma camera to locate lymph nodes with precision. 18 - 20 …”
Section: Introductionmentioning
confidence: 99%
“…The introduction of radiocolloid allows surgeons to perform preoperative lymphoscintigraphy to help guide surgical planning. 16,17 Moreover, it enables surgeons to employ intraoperative handheld gamma probe with or without an intraoperative portable gamma camera to locate lymph nodes with precision. [18][19][20] Earlier studies have shown that although radiocolloid tracers alone have an excellent rate of detecting SLNs, a combination with vital blue dye may increase the detection rate slightly.…”
Section: Introductionmentioning
confidence: 99%
“…The significance of the SLN concept is that a radical lymph node dissection with increased morbidity can be spared if the SLNB is negative. Although blue dye or isosulfan blue (Lymphazurin™) was used in the original study for melanoma SLN procedure [ 2 ], the critical development was the adoption of radiotracer [ 5 , 6 ] to identify SLNs. Technetium-99m sulfur colloid was widely used as it serves two major goals: (1) the ability to define the drainage patterns of the primary cancer site such as melanoma [ 6 ] or breast cancer to the regional nodal basin preoperatively and (2) facilitation of intraoperative identification of SLNs using a gamma probe [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…SLN biopsy (SLNB) is an established technique for tumor staging in patients with breast cancer. 2 The SLN is often identified using a radioactive isotope tracer (technetium 99m , Tc 99 ) and a blue dye (BD), patent blue V ® . The SLN is then detected with a handheld gamma probe, and the BD helps to visualize the SLN during surgery.…”
mentioning
confidence: 99%